Land use and vegetation changes in three Mexican Basins with Markov Models - Von Thaden Ugalde, Juan José; Lithgow, Debora; Revollo-Fernández, Daniel A.; Salazar-Vargas, María del Pilar; Rodríguez de los Santos, Aram (Instituto de Ecología, A.C., 2023)
In recent decades, anthropogenic activity has driven deforestation or the replacement of natural ecosystems, particularly forests, subsequently diminishing their capacity to provide a range of environmental services crucial for ensuring human well-being. Understanding land-use change dynamics and identifying its key drivers are essential for devising region-specific strategies. The main objective of this study was to understand and predict land-use and vegetation change dynamics in three basins in Mexico (Ameca-Mascota in Jalisco, Del Carmen in Chihuahua, and Jamapa in Veracruz), each exhibiting different levels of deforestation over a period of 25 years. This included analyzing historical trends, identifying biophysical and socioeconomic factors contributing to deforestation, and assessing future deforestation scenarios for 2026 and 2041 using Markov chains. Our findings suggest that land-use and vegetation change dynamics over the past 25 years lean toward deforestation, and future projections indicate that this deforestation trend is unlikely to change for the years 2026 and 2041. The two most significant drivers in all three basins were distance to roads and the vegetation edges, suggesting that deforestation is higher in areas close to roads and vegetation edges. This information is pivotal for developing conservation and restoration strategies in the three basins to reverse the current and future deforestation trends.